A recombinant Fasciola gigantica 14-3-3 epsilon protein (rFg14-3-3e) modulates various functions of goat peripheral blood mononuclear cells - Tian, Ai-Ling; Lu, MingMin; Calderón-Mantilla, Guillermo; Petsalaki, Evangelia; Dottorini, Tania; Tian, XiaoWei; Wang, YuJian; Huang, Si-Yang; Hou, Jun-Ling; Li, XiangRui; Elsheikha, Hany M.; Zhu, Xing-Quan (BioMed Central, 2018)
Background